O marketing ambiental e a construção de marca ecologicamente sustentável: uso da sustentabilidade pela marca Starbucks. - BARREIRA, Gabrielle Nunes Barreira (Universidade Federal do Tocantins, 2023)
The awakening of environmental awareness, influenced by the conjuncture from the sixties onwards, there has been the advancement of the environmental agenda on the international scene, the involvement of the environmental mass media for changing consumer behavior which is now concerned with the risks threats environmental issues as part of their purchasing decisions. In this way, it will promote a challenge based on green use, or will it become a reality in promoting ecological practices based on a new form of use. In this context, the present work aims to comprehend the purpose of green marketing regarding the application of sustainability the business sector, in a special context to analyze the relationship between the discourse and the environmental practice of the Starbucks Company, to answer the following question: How does the adherence to environmental marketing as an environmental discursive strategy contribute to socio-environmental responsibility gains and positioning of the referred company before the makert and consumer?. It is argued that by committing a social enviromental mission, Starbucks, mannaged to strengthen its power to infiltrate comunities and improve its reputation with stakeholders. In addition, the importance of the green consumer is pointed out, as na actor who has the ability to encourage the reflective capacity of citizes, societies and the State, regarding the problem of ecologically destructive economic growth, and sharing ecologically sustainable values. To answer the question and achieve the proposed objective, of the research, the case study of qualitative and bibliographic knowledge was considered the best.